Inhibitory immune checkpoints in preeclampsia: current landscape, mechanisms, and clinical perspectives - Mi Liu; Guikai Duan; Xiaomin Lai; Bingying Lin; Xiang Li; Jie Yang; Shu Cao; Hao Chen; Tong Wang; Bingyan Chen; Zhihua He; Qinglin Ma; et al. (Frontiers in Immunology, 2026)
Preeclampsia (PE) is a pregnancy-specific disorder whose pathogenesis remains incompletely elucidated. The prevailing theory suggests that compromised maternal-fetal immune tolerance is a key contributor. In recent years, inhibitory immune checkpoints have garnered considerable attention as key regulatory factors in maintaining immune homeostasis during pregnancy. Programmed cell death protein 1 (PD-1), T cell immunoglobulin and mucin domain-containing protein 3 (Tim-3), cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), T cell immunoreceptor with Ig and ITIM domains (TIGIT), and lymphocyte-activation gene 3 (LAG-3) are well-established inhibitory immune checkpoints in reproductive immunology. Additionally, emerging co-inhibitory molecules such as B- and T-lymphocyte attenuator (BTLA) and V-domain Ig suppressor of T cell activation (VISTA) have been increasingly implicated in the regulation of maternal-fetal immune tolerance. This review focuses on dissecting the mechanisms of inhibitory immune checkpoints in preeclampsia as well as their functions in maternal-fetal immune regulation. We evaluate their potential as early diagnostic biomarkers and novel targets for immunotherapy, highlight the limitations of existing relevant investigations, and outline critical pathways for subsequent clinical translation, offering insights into precision prophylaxis and treatment of preeclampsia.